Effectiveness of Structured Teaching Program on Knowledge and Practices on Menstrual Hygiene among Adolescent Schoolgirls in Government Schools of Lalitpur - Maharjan, Susan; Maharjan, Manju; Shrestha, Niran; Singh, Sarita; Shrestha, Rajani (Birat Journal of Health Sciences, 2020)
Introduction: Adolescent girls often have lack of knowledge and practices regarding reproductive health including menstruation. Objectives: To evaluate effectiveness of structured teaching program (STP) to increase level of knowledge and practices on menstrual hygiene among adolescent school girls. Methodology: Pre-experimental one group pre-posttest study design was applied in four government schools using power analysis for sample size calculation. Data were re- checked for its consistency and analyzed. Descriptive statistical methods were used for describing sample characteristic and inferential statistics was used to evaluate effectiveness of STP. Chi-squared test was used to examine association between selected demographic variables and pretest knowledge level of adolescent girls on menstrual hygiene. Result: The mean age of participants was 13.79 ±1.3 years (range from 11-18 years). Distribution of pre-test knowledge among respondents regarding menstrual hygiene showed, 49.21% moderate and 50.79% adequate knowledge respectively. In the case of post-test, all of them demonstrated adequate knowledge and none of them showed inadequate knowledge. Pre-test practices among respondents regarding menstrual hygiene recorded as 3.75% inadequate, 61.25% moderate and 35.0% adequate practices. The pre-test mean score for the level of knowledge was 13.36±1.64, whereas the post-test mean score was 15.8±0.73. Practice related pre-test mean score was 10.66±1.81 in comparison to, post-test mean score 13.34±0.75. There was no significant association found between knowledge regarding menstrual hygiene among adolescents with socio-demographic variables at p<0.05 level. Conclusion: It is concluded that the Structured Teaching Program is an effective strategy to improve knowledge and practice regarding menstrual hygiene for adolescent girls.